Análisis arqueoastronómico del templo de Queneto para determinar su relación con el sol, en el valle de Virú, La Libertad. - Asmat Vásquez, Edwin Rolando (2019)
This thesis report corresponds to the results of the study of the Queneto Temple, located in the San Juan stream, Virú Valley, La Libertad (Peru). The studies carried out to this place indicate that it was a Temple linked to solar observation, and possibly stellar and lunar. Through the use of Huancas or standing stones, which allowed to mark orientations in the natural horizon of the left bank of the Virú River, the programming of their economic, social and political activities was achieved within a structured ritual cycle. By means of the architectural, archaeoastronomical analysis and the simulation in the software, it was possible to define that the Queneto Temple would present a public space (Plazoleta A), destined for the realization of the ceremonies and rituals in the presence of the Huanca mayor (H1A), that would represent his ancestor or solar god. A restricted space (Plazoleta B) only for the one who operated the temple, which would serve as a place for observing the sun in its equinoctial and solstitial positions, and possibly stellar and lunar observations. And two places for rest and meditation (Environment A and B) intimately related to the platform B.